2014
DOI: 10.1021/es405428t
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Photosynthesis Inhibitors of Pelagic Marine Algae Using 96-Well Plate Microfractionation for Enhanced Throughput in Effect-Directed Analysis

Abstract: Because of large-scale production and use of an increasing diversity of chemicals in modern society, estuarine and coastal waters may be contaminated with numerous substances. Some of these compounds have the potential to affect microalgae at the base of the pelagic food chain. Therefore, we identified the main chemical stressors that negatively affect the effective photosystem II efficiency (ϕPSII) in marine microalgae of the Dutch estuarine and coastal waters. An enhanced effect-directed analysis (EDA) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 25 publications
1
51
0
1
Order By: Relevance
“…This approach is very time-consuming, and therefore an interesting alternative is a microfractionation system that combines LC or even LC×LC separations with a simultaneous collection of fractions in microtiter plates for effect analysis that allows for linking of effect and chemical identity [4244]. The applicability of such a system has already been demonstrated for high-throughput screening of several end points relevant in aquatic systems.…”
Section: Is What We Measure Relevant After All?mentioning
confidence: 99%
“…This approach is very time-consuming, and therefore an interesting alternative is a microfractionation system that combines LC or even LC×LC separations with a simultaneous collection of fractions in microtiter plates for effect analysis that allows for linking of effect and chemical identity [4244]. The applicability of such a system has already been demonstrated for high-throughput screening of several end points relevant in aquatic systems.…”
Section: Is What We Measure Relevant After All?mentioning
confidence: 99%
“…From these plots (data not shown) the CF at EC 10 level was determined (CF EC 10 ). Assuming, as demonstrated by Booij et al (2014), that the 6 key contaminants are responsible for the observed effect, the ΣTU EC 10 in the PAM assay is calculated with Eq. (3).…”
Section: Toxic Pressurementioning
confidence: 99%
“…Typical endpoints in EDA include, but are not limited to, endocrine disruption (Chapter 15), fish embryo toxicity (Zielke et al, 2011) mutagenicity, and aryl hydrocarbon receptor effects (Brack et al, 2005). Recent examples of EDA applications have been published by Booij et al (2014b) and Fetter et al (2014). EDA has also been applied in the context of the EU WFD (Brack et al, 2007(Brack et al, , 2015.…”
Section: : Organic Priority Hazardous Substances and Their Associatedmentioning
confidence: 99%